2020
DOI: 10.1097/ccm.0000000000004077
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Team Leadership Training Improves Team Leadership During Actual Trauma Resuscitations: A Randomized Controlled Trial

Abstract: Objectives: Trauma resuscitations are complex critical care events that present patient safety-related risk. Simulation-based leadership training is thought to improve trauma care; however, there is no robust evidence supporting the impact of leadership training on clinical performance. The objective of this study was to assess the clinical impact of simulation-based leadership training on team leadership and patient care during actual trauma resuscitations. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…One study was reported in two papers [49,50]. Fernandez et al (2020) [54] reported on the development of the intervention used in their study (Rosenman et al, 2019). All the manuscripts were published in English.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study was reported in two papers [49,50]. Fernandez et al (2020) [54] reported on the development of the intervention used in their study (Rosenman et al, 2019). All the manuscripts were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…The retained studies were published between 2009 and 2020 (see Table 1). Studies were conducted in Australia [39], Belgium [55], France [56], Germany [40,57], New Zealand [41], United States [42][43][44][45][46][47][48][49][50][51][52]54], Singapore [58], and Taiwan [53]. Key study characteristics are presented in Table 1 and outlined below.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations